Challenges and opportunities for the utilisation of ionic liquids as solvents for CO2 capture. Issue 3 (10th May 2018) - Mota-Martinez, Maria T.; Brandl, Patrick; Hallett, Jason P.; Mac Dowell, Niall
Abstract : Ionic liquids (ILs) have been extensively evaluated in the lab for use in CO2 capture applications. In this contribution, we evaluate ILs from a process performance perspective, and identify key research priorities to be addressed if ILs are to be deployed at industrial scale. Abstract : Ionic liquids have been extensively investigated as promising materials for several gas separation processes, including CO2 capture. They have the potential to outperform traditional solvents, in terms of their capacity, selectivity, regenerability and stability. In fact, hundreds of ionic liquids have been investigated as potential sorbents for CO2 capture. However, most studies focus on enhancing equilibrium capacity, and neglect to consider other properties, such as transport properties, and hence ignore the effect that the overall set of properties have on process performance, and therefore on cost. In this study, we propose a new methodology for their evaluation using a range of monetised and non-monetised process performance indices. Our results demonstrate that whilst most research effort is focused on improving CO2 solubility, viscosity, a transport property, and heat capacity, a thermochemical property, might preclude the use of ionic liquids, even those which are highly CO2 -philic, and therefore increased effort on addressing the challenges associated with heat capacity and viscosity is an urgent necessity. This work highlights a range of potential challenges that ionic liquids will face before they can be applied at process scale, and identifies some key research opportunities.